Single nucleotide polymorphisms (SNPs) in the open reading frame (ORF) of prion protein gene (PRNP) in Nigerian livestock species - Adeniyi C. Adeola; Semiu F. Bello; Abdussamad M. Abdussamad; Rahamon A. M. Adedokun; Sunday C. Olaogun; Nasiru Abdullahi; Akanbi I. Mark; Anyebe B. Onoja; Oscar J. Sanke; Godwin F. Mangbon; Jebi Ibrahim; Philip M. Dawuda; et al. (BMC Genomics, 2024)
Abstract Background Prion diseases, also known as transmissible spongiform encephalopathies (TSEs) remain one of the deleterious disorders, which have affected several animal species. Polymorphism of the prion protein (PRNP) gene majorly determines the susceptibility of animals to TSEs. However, only limited studies have examined the variation in PRNP gene in different Nigerian livestock species. Thus, this study aimed to identify the polymorphism of PRNP gene in Nigerian livestock species (including camel, dog, horse, goat, and sheep). We sequenced the open reading frame (ORF) of 65 camels, 31 village dogs and 12 horses from Nigeria and compared with PRNP sequences of 886 individuals retrieved from public databases. Results All the 994 individuals were assigned into 162 haplotypes. The sheep had the highest number of haplotypes (n = 54), and the camel had the lowest (n = 7). Phylogenetic tree further confirmed clustering of Nigerian individuals into their various species. We detected five non-synonymous SNPs of PRNP comprising of G9A, G10A, C11G, G12C, and T669C shared by all Nigerian livestock species and were in Hardy-Weinberg Equilibrium (HWE). The amino acid changes in these five non-synonymous SNP were all “benign” via Polyphen-2 program. Three SNPs G34C, T699C, and C738G occurred only in Nigerian dogs while C16G, G502A, G503A, and C681A in Nigerian horse. In addition, C50T was detected only in goats and sheep. Conclusion Our study serves as the first to simultaneously investigate the polymorphism of PRNP gene in Nigerian livestock species and provides relevant information that could be adopted in programs targeted at breeding for prion diseases resistance.